An Investigation of Tax-Related Corporate Political Activity in China: Evidence From Consumption Bribery. (January 2023) - Tang, Tanya Y. H.
This article investigates the occurrence and outcomes of corporate tax-related political activity through bribery. Specifically, it examines the extent to which firms bribe government officials through gift-giving, banqueting, and entertaining activities and the extent of payoffs that firms gain from these bribery practices. Using a large hand-collected dataset of Chinese listed firms for the period from 2009 to 2014, I find that firms that spend more on consumption bribery exhibit a significantly lower tax burden. This negative association is mainly driven by small firms, non-state-owned firms, state-owned firms with weak political connections, and firms in competitive industries. Further evidence shows that the tax benefits from bribery are more apparent in more corrupt, less economically developed, and less liberalized regions. Furthermore, the payoffs of tax bribery are mitigated by 45.4% after the implementation of China's anti-corruption campaign in 2012. These findings have policy implications for governments to optimize investment environments and increase tax revenue by curbing power-for-money deals.